2009
DOI: 10.1007/s12576-009-0057-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined resistance and aerobic training on reactive hyperemia in men

Abstract: Reduced response to reactive hyperemia (RH) in the extremities reflects impaired endothelium-dependent vasodilation of the microvasculature. The aims of the present study were to determine whether resistance training and a combination of aerobic and resistance training increase the endothelial vasodilation of the forearm assessed by RH. A total of 39 young men were assigned to either high-intensity resistance training (HIR; six types of exercises, 80% 1RM x 10 repetitions x 3 sets, n = 14) or moderate-intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The increase in forearm blood flow and reduction in forearm vascular resistance after the sessions of resistance exercise in this study corroborate the findings of Kawano et al, 36 Moraes et al, 35 and Heffernan et al 29 The moderate intensity and high volume of this exercise protocol promoted improvement in vasodilator response, as measured by blood flow. A study by Tanimoto and Ishii 46 demonstrated that prolonged resistance exercise with low intensity, slow movements, and tonic force generation in muscle induced muscle hypertrophy via the hypoxic environment, and could result in angiogenesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increase in forearm blood flow and reduction in forearm vascular resistance after the sessions of resistance exercise in this study corroborate the findings of Kawano et al, 36 Moraes et al, 35 and Heffernan et al 29 The moderate intensity and high volume of this exercise protocol promoted improvement in vasodilator response, as measured by blood flow. A study by Tanimoto and Ishii 46 demonstrated that prolonged resistance exercise with low intensity, slow movements, and tonic force generation in muscle induced muscle hypertrophy via the hypoxic environment, and could result in angiogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that different isolated or combined physiological pathways have contributed to such a phenomenon. Among them, there is already enough evidence that microvascular changes, 36 reduced cardiac output resulting from decreased stroke volume, 30 and blood lactate concentration 37 are related to post-exercise hypotension. Moreover, it is known that neural parameters, such as reduced sympathetic activation, and humoral parameters, such as greater bioavailability of nitric oxide 12 and antioxidant compounds, are well established mechanisms involved in post-exercise hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Although normally associated with muscle fiber hypertrophy, resistance exercise can also stimulate vascular adaptations. Resistance exercise training alters vascular structure and function, with increases in muscle capillarization (11), reactive hyperemia (19), and flow-mediated vasodilation (31). Acute bouts of resistance exercise increase angiogenic growth factor expression in muscle and in the circulation (10).…”
mentioning
confidence: 99%
“…The stresses experienced by the vascular system in response to resistance exercise are likely to vary depending on the forces generated, number of repetitions completed, and recovery period allowed (19). Indeed, suitably structured resistance workouts that emphasize light to moderate resistance, high repetitions, and short recoveries as part of a muscular endurance workout may result in a greater ischemic stimulus in a wider range of muscle groups than that occurring during aerobic exercise.…”
mentioning
confidence: 99%
“…Furthermore, it may be that isolated and/or combined physiological pathways may interfere with this reduction. There are some indications of improved availability of nitric oxide, increased prostaglandins decreased endothelin 1 and changes in vessel resistance 36,37 , in addition to a reduction in cardiac output due to a decrease in systolic volume and microvascular changes 38,39 that may explain this BP decrease.…”
Section: Blood Pressure Measurement and Mechanismmentioning
confidence: 99%